Quinoxaline-based anti-schistosomal compounds have potent anti-plasmodial activity - Rawat, Mukul; Padalino, Gilda; Adika, Edem; Okombo, John; Yeo, Tomas; Brancale, Andrea; Fidock, David A; Hoffmann, Karl F; Lee, Marcus C S (PLoS pathogens, 2025)
The human pathogens Plasmodium and Schistosoma are each responsible for over 200 million infections annually, especially in low- and middle-income countries. There is a pressing need for new drug targets for these diseases, driven by emergence of drug-resistance in Plasmodium and an overall dearth of drug targets against Schistosoma. Here, we explored the opportunity for pathogen-hopping by evaluating a series of quinoxaline-based anti-schistosomal compounds for their activity against P. falciparum. We identified compounds with low nanomolar potency against 3D7 and multidrug-resistant strains. In vitro resistance selections using wildtype and mutator P. falciparum lines revealed a low propensity for resistance. Only one of the series, compound 22, yielded resistance mutations, including point mutations in a non-essential putative hydrolase pfqrp1, as well as copy number amplification of a phospholipid-translocating ATPase, pfatp2, a potential target. Notably, independently generated CRISPR-edited mutants in pfqrp1 also showed resistance to compound 22 and a related analogue. Moreover, previous lines with pfatp2 copy number variations were similarly less susceptible to challenge with the new compounds. Finally, we examined whether the predicted hydrolase activity of PfQRP1 underlies its mechanism of resistance, showing that both mutation of the putative catalytic triad and a more severe loss of function mutation elicited resistance. Collectively, we describe a compound series with potent activity against two important pathogens and their potential target in P. falciparum.
Keywords: Animals; léková rezistence; Plasmodium falciparum; chinoxaliny; Drug Resistance; lidé; antimalarika; zvířata; tropická malárie; Malaria, Falciparum; Antimalarials; Quinoxalines; Humans